Digital signal processing using MATLAB - Schilling, Robert J.; Harris, Sandra L. (South-Western/Cengage Learning, 2017)
Focus on the development, implementation, and application of modern DSP techniques with DIGITAL SIGNAL PROCESSING USING MATLAB (R), 3E. Written in an engaging, informal style, this edition immediately captures your attention and encourages you to explore each critical topic.